Multicriteria Analysis to Determine Locations of Restaurant Branch Using Bayesian Network - Fauzia, Nilna; Singgih, Moses Laksono (Institut Teknologi Sepuluh Nopember, 2020)
To determine a strategic restaurant location, a company has to consider several location criteria. Location criteria is divided into two perspective, namely customer perspective and management perspective. The purpose of the consideration of restaurant location criteria are to attract customer to come in so could obtain maximum profit for the unit business. Every restaurant has different location criteria, that is influenced by market segmentation of restaurant and business strategic of the company. The aim of this research is to learn about general restaurant location criteria, investigate specific restaurant location criteria, and do an assessment to obtain appropriate location alternative. Specific restaurant location of this research is location of Ayam Geprek â€œAGâ€ Restaurant. This research use Bayesian Network Method to process probability of the criteria. This research obtain the data from questionnaire to management and potential customer Ayam Geprek â€œAGâ€ Restaurant. The questionnaire consist of two steps, the first step is choices for Ayam Geprek â€œAGâ€ criterion restaurant. The second questionnaire is about level of importance assessment every location criteria. There are three alternative location that will be rated based on the Ayam Geprek â€œAGâ€ criteria. The result for the appropriate alternative is third alternative which are located in west Surabaya and has total score 18.11.